The cabinet of eros: Renaissance mythological painting and the Studiolo of Isabella d'Este - Campbell, Stephen John (Yale Univ. Press, 2006)
Introduction. Placing the gods -- Pt. 1. The studiolo and its histories. The study, the collection, and the Renaissance self -- Myth and the articulation of gender and space -- Isabella's "cupidity" : collecting and literary production -- Pt. 2. The paintings. Mantegna's Mars and Venus : poetry, natural history, and the origins of art -- Mantegna's mythic signatures : Pallas and the vices -- Tanta amorosa impresa : Isabella, Perugino, and Paride da Ceresara -- Lorenzo Costa's coronation of a woman poet and the Renaissance of Sappho -- "Sweet counterfeiting and blandishments" : courtiership, urbanitas, and Costa's Comus -- "Dominate the stars" Correggio, the Gonzaga, and the sack of Rome -- Conclusion. The rise of mythological painting in sixteenth-century Italy